HAK ASASI MANUSIA SEBAGAI JUS COGENS DAN KAITANNYA DENGAN HAK ATAS PENDIDIKAN - Virgayani Fattah (Yuridika, 2017)
Jus cogens as a norm of general international law accepted and recognized by the community as a whole interasional with the main characteristics are non-derogable nature. The right to education is a fundamental human rights, so that its presence can not be reduced under any circumstances based on the benefits and importance of education for children. The national education policy is not fully aligned with the international human rights instruments led to the development of the education sector is not entirely based on human rights. Government is obliged to fulfill the right to education, especially with regard to the budget for building and repairing school buildings and improve the quality of education in Indonesia. The importance of the right to education as the main vehicle for elevating and empowering children from poverty, as a means to actively participate in the construction and total social community and as a powerful path towards human civilization itself. So it can be understood that a peremptory norm, also called jus cogens is a basic principle of international law that is considered to have been accepted in the international community of the country as a whole. Unlike general treaty law that traditionally requires treaties and allows for changes in obligations between countries through treaties, peremptory norms can not be violated by any country.